Toward a relevant agenda for warehousing research: literature review and practitioners' input - Hoda Davarzani; Andreas Norrman (Logistics Research, 2015)
The main purpose of this research is to provide an agenda for future warehousing research relevant for both academic development and practitioners' needs. In order to suggest a practically relevant future research agenda, first a comprehensive literature review was performed to identify research areas covered in the literature. Then, 15 warehouse managers and senior consultants were interviewed to add empirical input to the development of potential future research areas. The literature review reveals gaps, both methodology- and topic-wise. A considerable methodological imbalance is observed. Some of the highlighted managerial concerns have been investigated in the literature extensively, but the managerial concerns emphasized mostly do not belong to the most researched categories. While most of the practitioners' concerns relate to supportive aspects of warehousing business, a relatively high number of the reviewed studies highlight operational problems. The suggested future research agenda highlights the importance of supportive aspects of the warehousing business, employment of real data in analysis and empirical research methods. The insights from practitioners stress the expected trends of business environment such as more volatile demand, higher desire for customized services and more expansion of e-commerce.
Keywords: 650; Literature review; Research agenda; Warehousing; Material handling